Inhibitory Activity of Sargassum hystrix Extract and Its Methanolic Fractions on Inhibiting α-Glucosidase Activity - Azizi, Wirdatul Auliya; Ekantari, Nurfitri; Husni, Amir (Indonesian Journal of Pharmacy, 2019)
Seaweed has a great potential in the pharmaceutical field, one of them as antidiabetic. The purposed of this study was to know the inhibitory activity of Sargassum hystrix extract and its methanol fraction in inhibiting α-glucosidase activity. S. hystrix was extracted using methanol, then partitioned using chloroform, ethyl acetate, and methanol. Methanol fraction then separated by column chromatography to obtain the compound. The crude extract, the partitioned methanol fraction, and the column chromatography fraction were tested for its activity on inhibiting the α-glucosidase. The compounds of active fraction were analyzed using gas chromatography-mass spectrometry (GC-MS). The inhibitory activity (IC50) of the crude extracts and the partitioned methanol fraction were 0.35±0.05 and 0.02±0.00 (mg/mL), respectively. The column chromategraphy fractions that had an inhibitory activity to α-glucosidase were M2 (23.46±1.63%), M3 (30.88±4.53%), M4 (73.64±3.47%), and M7 (53.48±1.56%). GC-MS showed that the suspected compound which had inhibiting α-glucosidase in methanol fraction were 9-Octadecenoic acid, 1-Heptadecanecarboxylic acid,9,12-Octadecadienoic acid (Z, Z), and Octadecanoic acid methyl ester.